Association of Asthma and Quality of life among Asthma Affectees - Noureen Farooq, Ayesha Sajid, Humaira Aftab, Summaiya Malik Zaman, Azaz Ullah Shah, Firasha Ayub (Pakistan Journal of Medical & Health Sciences, 2023)
Asthma is one of the most widespread respiratory ailments characterized by persistent inflammation, breathing difficulty, and airway hypersensitiveness. Critical and poorly controlled asthma influence the quality of life (QoL) of patients. The study aimed to evaluate asthma control and its association with the quality of life of the affectees. Methods: A single cross-sectional survey was carried out at Lady Reading Hospital Peshawar from November 2019 to January 2020. 217 participants participated in a study. The survey was conducted by 217 using a convenience sampling technique. The asthma score scale and WHOQOL BREF-100 were used to collect data. Results: Out of 217, 136(62.7%) males and 81(37.3%) females participated in study. Mean age of the participants was 42.98± 19.26. Almost half of the responder’s family reported positive asthma family history (101=46.5%). The mean Asthma Score (Asthma Control Test) was 15.86±4.02. The current study reported relatively poor quality of life in social Relations 48.21±14.58 and environment 42.85± 8.56 domains. Data regarding correlation showed a non-significant but positive association between asthma control and physical health, social relations, environment-related domains of WHOQOL but a non-significant negative association was found between asthma control score and psychological health. Practical Implication: The findings showed a relatively poor quality of life in social and environmental domains. Moreover, a positive association was found between the asthma score and Physical Health, Social Relations, Environment related domains of WHOQOL Conclusions: Majority of the participants had well-controlled asthma symptoms. The study findings regarding WHOQOL showed he relatively poor quality of life in social and environmental domains. Moreover, a positive association was found between the asthma score, physical health, social relations, environment-related domains of WHOQOL. Practical Implication: Asthma affects quality of life among affectees. This study helps patients, physicians and cardiopulmonary physical therapist to understand the impact of asthma on quality of life of a asthmatic. Keywords: Asthma, Health related quality of life, Physical health, psychological health, Quality of life.